2019
DOI: 10.1016/j.resconrec.2018.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Which US municipalities adopt Pay-As-You-Throw and curbside recycling?

Abstract: This study investigates the drivers of curbside recycling program adoption and Pay as You Throw (PAYT) program adoption in 1,856 US local governments using a 2015 survey. While 50% of municipalities and counties adopt curbside recycling programs, we find that the adoption of curbside recycling is limited by capacity constraints; local governments with lower per capita public expenditures and more poverty are less likely to implement curbside recycling. PAYT programs are less common overall (10% of municipaliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 34 publications
0
9
1
Order By: Relevance
“…Men’s probability of “never segregating waste” is 0.031 higher than women’s, and men are 0.014 less likely to segregate waste often. Besides, it is generally believed that more educated individuals are more sensitive to social welfare and would exhibit more pro-environmental behaviors [ 46 , 53 , 54 ]. As seen in Table 4 , compared to illiterate respondents, the probability of “often segregating waste” is on average 0.016 times higher for those who have attended primary school, 0.039 times higher for the group who have attended junior high school, 0.065 times higher for those who have attended high school, and 0.071 times higher for those with a college degree or above.…”
Section: Resultsmentioning
confidence: 99%
“…Men’s probability of “never segregating waste” is 0.031 higher than women’s, and men are 0.014 less likely to segregate waste often. Besides, it is generally believed that more educated individuals are more sensitive to social welfare and would exhibit more pro-environmental behaviors [ 46 , 53 , 54 ]. As seen in Table 4 , compared to illiterate respondents, the probability of “often segregating waste” is on average 0.016 times higher for those who have attended primary school, 0.039 times higher for the group who have attended junior high school, 0.065 times higher for those who have attended high school, and 0.071 times higher for those with a college degree or above.…”
Section: Resultsmentioning
confidence: 99%
“…This share increased substantially from 16 percent in 1999 [4]. This is different to the United States, where in 2015, only 10% of municipalities had unit-based pricing or pay-as-youthrow [5].…”
Section: Introductionmentioning
confidence: 80%
“…In addition, some studies suggest that individuals supporting conservative ideologies were less likely to support policies to bolster sustainability compared to liberal-oriented individuals (Ziegler, 2017). Conversely, Gradus et al (2019), suggested that local political affiliation did not play a role in adopting a pay-as-you-go recycling program that helps increase recycling efficiency. Future exploration is needed to further understand this finding and identify whether this discrepancy could be due to liberal states being more in favor of sustainability policies compared to conservative states.…”
Section: Discussionmentioning
confidence: 99%